Pengaruh Servant Leadership, Perceived Organizational Support, Leader Member Exchange, Dan Psychological Empowerment Pada Organizational Citizenship Behavior - Sari, Sekar; Soni Kurniawan, Ignatius; Purnamarini, Tri Ratna (Universitas Hamzanwadi, 2024)
The point of this study is to look into how organizational citizenship behavior (OCB) is affected by servant leadership, LMX (leader-member exchange), physical empowerment (PE), and perceived organizational support (POS). This study uses a population of employees of the Agriculture and Food Service Office of Yogyakarta City, with 62 research respondents. The sampling technique uses accidental sampling or is filled by respondents who are willing to be involved. Data were collected using a questionnaire and processed using multiple linear regression analysis and the SPSS 23 application. The results confirmed that POS and PE positively influenced OCB. Servant leadership was found to have a negative effect, while LMX had no significant effect on OCB. The implications of the research results lead to strengthening POS and PE to strengthen employee OCB.